THE EFFECT OF BOGGLE GAMES ON THE VOCABULARY MASTERY OF THE SEVENTH GRADE STUDENTS' AT MTS. NURUL HIKMAH - Nurul Komariayul Soliha; Abdul Rohim (Universitas Muhammadiyah Tangerang, 2021)
AbstractThe research is aimed to investigate whether there is an effect of the Boggle game on vocabulary mastery of seventh-grade students at MTs. Nurul Hikmah. The design used was quasi-experimental method with Nonequivalent control group design. The subject of population in this research is seventh-grade students of MTs Nurul Hikmah. The sample of this research were 60 students, who were classified into 30 students of experimental class and 30 students of controlled class. The technique of collecting data with used the research instrument was a test consisting of a pre-test and post-test. The results of thisresearch stated that the used of Boggle games in learning vocabulary affected students' vocabulary mastery. This can be seen from the t-test results of pre-test and post-test at a significance level of 5% (0.05) alpha and degrees of freedom of 2.00, where the t-count of pre-test is higher than the t-table (2.03 > 2.00) with the average pre-test score of the experimental class was higher than the average pre-test score of the control class (49.47 > 42.60) and the t-count of post-test is higher than the t-table (5.75> 2.00) with the average post-test score of the experimental class was higher than the average pre-test score of the control class (83.50 > 73.10). It can be concluded that there is significant effect of Boggle game on the seventh grade students’ vocabulary mastery at MTs. Nurul Hikmah. It means that the Boggle game is effective in learning vocabulary mastery for the seventh-grade students of MTs Nurul Hikmah. By using the Boggle game, the teaching and learning process becomes more interesting. Key words: Boggle Game, Vocabulary Mastery.